Isolation and Identification of bacterial isolates from ear infection and their sensitivity to usual antibiotics in human and dogs - B. S., AL- Nassry (The Iraqi Journal of Veterinary Medicine, 2011)
Bacterial examination was done on 50 dogs suffering from ear infection. Dogs examined include both sexes and their ages were between 5 months to 5 years, In the other hand 35 ear smears from male and female human in ages between 7-40 years were also taken . Isolation and identification of bacterial isolates were done to determine species of zoonotic bacteria in human and dogs, also study of antibiotics sensitivity to these isolates. We identified 137 bacterial isolates from dogs ear belonge to 9 bacterial spp. which are : S. aureus( 27.7%) , Klebsiella spp. ( 13.8%) , E. coli ( 13.1%) , Streptococcus spp. ( 12.4%) ,P. haemolytica ( 8.2%) , P. vulgaris ( 7.2%) , S. epidermidis ( 6.5%) , Salmonella spp. ( 5.8%) , P. mirabilis ( 5.1%) . In human ear smears 95 isolates were identified to 11 bacterial spp. as follows : S. aureus( 26.3%) , Streptococcus spp. ( 15.7%) , S. epidermidis ( 13.6%) , Citrobacter spp. ( 9.4%) , P. mirabilis ( 8.4%) , Klebsiella spp. ( 6.3%) , P. vulgaris ( 5.2%) , Salmonella spp. ( 5.2%) , P. aeruginosa ( 4.2%) , Shigella spp. ( 3.1%) , E. coli ( 2.1%) . Antibiotic sensitivity to dog isolates show high sensitivity to Imipenem (IPM) then Streptomycin ( S) then Rifampin ( RA) then Clindamycin ( DA) and lowest to Erythromycin ( E) respectively . but most isolates were resistant to Cefotaxime( CTX) then Ampicillin ( AM) then Vancomycin ( VA) and lowest to Trimethoprim ( TMP) respectively . The human isolates show high sensitivity to Imipenem ( IPM ) then Streptomycin ( S ) then Erythromycin ( E ) then Rifampin ( RA) then Clindamycin ( DA) finally Vancomycin ( VA) . but most isolates were resistant to Cefotaxime ( CTX ) then Ampicillin ( AM) finally Trimethoprim (TMP). P. aeruginosa was resistant to all antibiotics except Imipenem ( IPM) , Streptomycin ( S) and Erythromycin ( E)